Inclusive Insurance, Income Distribution, and Inclusive Growth - Lili Zheng; Ya Su (Frontiers Media S.A., 2022)
Financial inclusion, whereby all adults have effective access to financial products, including insurance, has increasingly become a global priority, particularly in low and middle income economies. This study matches the measured development level of inclusive insurance in Chinese provinces with China Family Panel Studies (CFPS) data and evaluates the impact of inclusive insurance on income distribution and inclusive growth. The findings support that inclusive insurance has a positive impact on income distribution and inclusive growth. The effect is more pronounced in eastern areas, rural areas and low-income households. The policy shocks and instrumental variables introduced prove the robustness of the results. PSM-DID test indicate that the inclusive insurance policy has a significant positive effect on income distribution. Alternative measure of inclusive insurance and GMM test with instrumental variables indicate that the results are robust. Additionally, we also find that there is a threshold effect on the impact of the inclusive insurance on income. When the universal insurance index exceeds the threshold value, the promoting effect on income is enhanced.